1997
DOI: 10.1177/07399863970194008
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Planning for College among Youth of Mexican Descent

Abstract: This research examined associations between acculturation, college planning, and college attendance in 410junior and senior high school students. Participants, of which three quarters were of Mexican descent and one quarter was of European descent, completed Cuellar; Harris, and Jasso's acculturation scale and a college-planning survey. Ten months later; 116 of the 148 participating seniors were interviewed to determine if they went to college and what resources helped them get there. Acculturation among Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 8 publications
3
47
2
Order By: Relevance
“…Existing research supports a relationship between acculturation status and academic achievement (e.g., Hurtado & Gauvain, 1997). However, no significant relationships were found in the present study when acculturation status was determined by the Felix-Ortiz et al (1994) measure.…”
Section: Acculturation and Academic Achievementcontrasting
confidence: 91%
See 1 more Smart Citation
“…Existing research supports a relationship between acculturation status and academic achievement (e.g., Hurtado & Gauvain, 1997). However, no significant relationships were found in the present study when acculturation status was determined by the Felix-Ortiz et al (1994) measure.…”
Section: Acculturation and Academic Achievementcontrasting
confidence: 91%
“…Research demonstrates that a high orientation to U.S. culture is related to academic success and predictive of college attendance among Mexican American high school students (Hurtado & Gauvain, 1997;Manaster & Chan, 1992). Other research illustrates that Mexican American adolescents who identify with both cultures equally (i.e., bicultural or integrated) have better educational attainment and academic achievement than those who identify almost solely with either culture (López et al, 2002).…”
Section: The Relationship Between Acculturation and Academic Achievementmentioning
confidence: 99%
“…Additionally, a study on Latina college students (Cardoza, 1991) did support the relation between mother's education level and educational aspirations. In contrast, a study on a sample of predominantly Mexican American high school students (Hurtado & Gauvain, 1997) revealed that father's education level significantly explained variance in college aspirations. Although mothers and fathers may play a different role in career development (O'Brien, Friedman, Tipton, & Linn, 2000), our study concluded that neither parent's education level uniquely predicted educational aspirations of Mexican American high school students.…”
Section: Se B Tmentioning
confidence: 77%
“…Gonzalez et al (2003) found that Latinas with increased access to cultural and social capital in school were more likely to enter selective universities; those who did not tended to choose community college. Students' level of acculturation may affect the ability to accumulate social and cultural capital via schools (Hurtado and Gauvain, 1997), leaving highly mobile and limited-English students at a disadvantage (Ream, 2003). In at least one study of Mexican-origin students, higher grades, expectations, and bilingual abilities were associated with greater access to valuable social capital (Stanton-Salazar and Dornbusch, 1995).…”
Section: School Community and Regional Contextsmentioning
confidence: 99%